(untitled) (SAARC Journal of Agriculture, 2015)
The experiment was conducted at the experimental site of Agronomy Department of the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during January to June 2010 to evaluate some important agronomic traits of one hundred and fifteen genotypes of soybean to screen out high yielding soybean genotypes. Considerable genetic variability was observed in the 115 germplasm. Depending on the variability in quantitative traits, the genotypes were grouped in six clusters. The genotypes which have greater morphological similarity were grouped in clusters. The results indicated the presence of high degree of divergence in the genotypes. The clustering pattern of the 115 soybean genotypes in six groups and their inter-group distances revealed that genotypes in Cluster III comprised of BARI Soybean 5, G00083, BARI Soybean 6, G00342, BD 2338, BD 2355, BD 2329, BD 2340, AGS 95, G00056, AGS 129, BD 2336, BGH 02026, BGM 02093, Galarsum, BD 2350, G00084, BD 2331, G00103 indicated better performance which could be marked for the selection of yield potential genotypes through further evaluation. DOI: http://dx.doi.org/10.3329/sja.v12i2.21921 SAARC J. Agri., 12(2): 90-100 (2014)